2018
DOI: 10.1016/j.ijmecsci.2018.05.049
|View full text |Cite
|
Sign up to set email alerts
|

The plane mixed problem for an elastic semi-strip under different load types at its short edge

Abstract: The mixed problem for the fixed semi-strip is investigated in this article for the three cases of the applied mechanical load. The solution of the boundary problem is reduced to the solution of the singular integral equation (SIE) with regard to the unknown displacements derivative. Three cases of SIE are investigated: when the mechanical load is applied on the center of the semi-strips edge, when the mechanical load is distributed near the left lateral side and when the mechanical load is distributed on the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The first singular integral equation in system (24) is the partial case of the equation with two fixed singularities. [39] The transcendental equation for the definition of the singularity indicator of the solution̂( ) was constructed. It is congruent to the transcendental equation presented in [40] for the problem of a wedge with the angle of openness ∕2.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…The first singular integral equation in system (24) is the partial case of the equation with two fixed singularities. [39] The transcendental equation for the definition of the singularity indicator of the solution̂( ) was constructed. It is congruent to the transcendental equation presented in [40] for the problem of a wedge with the angle of openness ∕2.…”
Section: Casementioning
confidence: 99%
“…The first singular integral equation in system is the partial case of the equation with two fixed singularities . The transcendental equation for the definition of the singularity indicator of the solution χ̂false(ξfalse) was constructed.…”
Section: The Solving Of the Ssiementioning
confidence: 99%
“…The boundary value problem in the theory of elasticity (and the theory of plate bending) for a half-strip or a rectangle, two opposite sides of which are firmly clamped and stresses are specified at the ends, has been the subject of numerous studies, especially in the period of 1960s to 1980s. Reviews can be found, for example, in previous studies [1][2][3][4][5][6]. Researchers were interested in the question of the singularity for stresses at the corner points of the regions under consideration, which are simultaneously the points of change in the type of boundary conditions.…”
Section: Introductionmentioning
confidence: 99%